Assessing the role of deoD gene in Mycobacterium tuberculosis in vitro growth and macrophage infection. (June 2018) - Dalberto, Pedro Ferrari; Rodrigues-Junior, Valnês; Almeida Falcão, Virginia Carla; Pinto, Antônio Frederico Michel; Abbadi, Bruno Lopes; Bizarro, Cristiano Valim; Basso, Luiz Augusto; Villela, Anne Drumond; Santos, Diógenes Santiago
Abstract: Purine nucleoside phosphorylase from Mycobacterium tuberculosis (MtPNP), encoded by deoD gene (Rv3307), is an enzyme from the purine salvage pathway, which has been widely studied as a molecular target for the development of inhibitors with potential antimycobacterial activity. However, the role of MtPNP in tuberculosis pathogenesis and dormancy is still unknown. The present work aims to construct a deoD knockout strain from M. tuberculosis, to evaluate the role of MtPNP in the growth of M. tuberculosis under oxygenated condition and in a dormancy model, and to assess whether deoD gene is important for M. tuberculosis invasion and growth in macrophages. The construction of a knockout strain for deoD gene was confirmed at DNA level by PCR and protein level by Western blot and LC-MS/MS. The deoD gene is not required for M. tuberculosis growth and survival under oxygenated and hypoxic conditions. The disruption of deoD gene did not affect mycobacterial ability to invade and grow in RAW 264.7 cells under the experimental conditions employed here. Highlights: A knockout strain for deoD gene was obtained by homologous recombination. deoD gene is not required for M. tuberculosis growth under oxygenated conditions. deoD deletion did not affect M. tuberculosis growth in an anaerobic dormancy model. deoD gene is not important for M. tuberculosis invasion and growth in macrophages.